1984
DOI: 10.7164/antibiotics.37.1692
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic hydrolysis of erythromycin by a strain of Escherichia coli. A new mechanism of resistance.

Abstract: Escherichia coil BM2195 is highly resistant to erythromycin by inactivation of the antibiotic. We have determined the structure of the modified antibiotic by physico-chemical techniques including mass spectrometry, infrared spectrophotometry, 13C nuclear magnetic resonance, and circular dichroism.The results obtained indicate that E. coli BM2195 resists erythromycin by the production of an erythromycin esterase which hydrolyzes the lactone ring of the antibiotic.Escherichia coli, like most Gram-negative bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 5 publications
2
40
0
1
Order By: Relevance
“…Resistance to macrolides can be based on different mechanisms: target modification by point mutation or methylation of 23S rRNA, thereby inhibiting the binding of macrolides [76], hydrolysis of the lactone ring in the macrolide [5], and efflux pumps removing the macrolide from the bacteria [60]. In Campylobacter it has been shown that resistance is not consistent with the presence of rRNA methylase, with modification of the antibiotic or with efflux [79].…”
Section: Macrolide Resistancementioning
confidence: 99%
“…Resistance to macrolides can be based on different mechanisms: target modification by point mutation or methylation of 23S rRNA, thereby inhibiting the binding of macrolides [76], hydrolysis of the lactone ring in the macrolide [5], and efflux pumps removing the macrolide from the bacteria [60]. In Campylobacter it has been shown that resistance is not consistent with the presence of rRNA methylase, with modification of the antibiotic or with efflux [79].…”
Section: Macrolide Resistancementioning
confidence: 99%
“…Colonization of the intestinal tract by members of the family Enterobacteriaceae that are highly resistant to erythromycin is usually associated with previous long-term oral therapy with the drug (2-4). It has been reported that high-level resistance to erythromycin in members of the family Enterobacteriaceae results from production of erythromycin esterases and rRNA methylases (1,5,(6)(7)(8)24).We reported previously that the structure of inactivated oleandomycin generated by erythromycin-resistant (MIC, 1,600 ,ug/ml) Escherichia coli Tf481A, which was isolated from a patient in Japan in 1983, was oleandomycin 2'-phosphate (22). This paper describes the purification and characterization of a new macrolide-inactivating enzyme, macrolide 2'-phosphotransferase [MPH(2')].…”
mentioning
confidence: 99%
“…Colonization of the intestinal tract by members of the family Enterobacteriaceae that are highly resistant to erythromycin is usually associated with previous long-term oral therapy with the drug (2-4). It has been reported that high-level resistance to erythromycin in members of the family Enterobacteriaceae results from production of erythromycin esterases and rRNA methylases (1, 5,[6][7][8]24).…”
mentioning
confidence: 99%
“…7). Addition of 1 pug of erythromycin per ml had no effect on [14C]niddamycin (4 However, inasmuch as previously published data on strain of medium and suspended in fresh medium at 37°C. 958-2 (20) left open the possibility that ribosome modifica-1 suspension media for ii and iii contained 1 ,ug of tion, intracellular macrolide degradation, and/or reduced ycin per ml.…”
Section: Methodsmentioning
confidence: 63%